Triage method for load rating bridge size two-cell reinforced concrete box culverts for the AASHTO LRFD design load. Issue 9 (2nd September 2023) - Sharifi, Hossein; Peiris, Abheetha; Harik, Issam
Abstract: Reinforced concrete bridge size box culverts (RCBCs), with structure length greater than or equal to 6.1 m (20 ft), are an integral part of the transportation infrastructure. Load rating RCBCs is essential, and the critical component is generally the top slab. The objective of this study is to propose a triage methodology to quickly and conservatively determine the rating factor ( RF ) for the top slab of a two-cell RCBC. The derivation of the demand equations is illustrated in this manuscript for the top slab and the AASHTO HL-93 live load. The finite element program CANDE is used to evaluate the influence of the cell clear height ( H ), cell clear span ( S ), fill height ( HF ), and the backfill modulus ( E ) on the demand loads. Multiple regression analyses showed that H had no significant effect on the dead load demands, while H and E had no significant effect to the live load demands. Conservative linear demand equations (LDEs) are presented to calculate the dead and live load demands leading to a quick determination of the RF . LDEs for single and multi-cell culverts can be derived following the LDE procedure outlined herein.